Analisis Potensi Pengembangan Pos Kesehatan Pesantren di Kota Medan - Purnama, Tri Bayu; Pertiwi, Arbitra Morlinda Rua (Journal of Religion and Public Health, 2021)
The degree of public health in Islamic boarding schools is still a problem. Limited information about the Pesantren Health Posts as health services in the Pesantren will hamper the improvement of the community's health status in the Pesantren. This study used a qualitative method with a case study design conducted at the Boarding School with the boarding system in Medan from October to December 2019. Research informants of 2 people in each Pesantren were purposive sampling with in-depth interviews and observation using interview guidelines and observation guidelines. Information is analyzed with content analysis and data presentation in the form of matrix tables and descriptive narratives. Based on the results of the study, Islamic Boarding Schools in Medan City still do not have Poskestren. Terminology Poskestren more commonly known as the UKS (School Health Unit), and the Santri and Community Medical Center (BPSM). However, based on Poskestren input indicators, Islamic boarding schools in Medan have great potential to be developed into Poskestren. The conclusion of the research is that there is no common perception about "Poskestren" so that based on the Ministry of Health in 2013 related to Poskestren, all pesantren in Medan City have not met the requirements of Poskestren. Therefore it is necessary to apply regulations and policies that have been set by the Ministry of Health related to the Poskestren in Pesantren that are fostered by the Puskesmas and to prepare human resources through training so that the Poskestren becomes the spearhead of Pesantren health.keywords: Analysis, Poskestren, MedanAbstrakDerajat kesehatan masyarakat di pondok pesantren masih menjadi masalah. Keterbatasan informasi tentang Posyandu sebagai pelayanan kesehatan di Pesantren akan menghambat peningkatan derajat kesehatan masyarakat di Pesantren. Penelitian ini menggunakan metode kualitatif dengan desain studi kasus yang dilakukan di Pondok Pesantren dengan sistem asrama di Medan dari bulan Oktober sampai Desember 2019. Informan penelitian sebanyak 2 orang di setiap Pesantren bersifat purposive sampling dengan wawancara mendalam dan observasi menggunakan pedoman wawancara dan pedoman observasi. Informasi dianalisis dengan analisis isi dan penyajian data dalam bentuk tabel matriks dan narasi deskriptif. Berdasarkan hasil penelitian, Pesantren di Kota Medan masih belum memiliki Poskestren. Terminologi Poskestren lebih dikenal dengan UKS (Unit Kesehatan Sekolah), dan Balai Kesehatan Santri dan Masyarakat (BPSM). Namun berdasarkan indikator input Poskestren, pesantren di Medan memiliki potensi besar untuk dikembangkan menjadi Poskestren. Kesimpulan dari penelitian ini adalah tidak adanya kesamaan persepsi tentang “Poskestren” sehingga berdasarkan Kementerian Kesehatan tahun 2013 terkait Poskestren, seluruh pesantren di Kota Medan belum memenuhi persyaratan Poskestren. Oleh karena itu perlu diterapkan peraturan dan kebijakan yang telah ditetapkan oleh Kementerian Kesehatan terkait Poskestren di Pesantren yang dibina oleh Puskesmas serta mempersiapkan SDM melalui pelatihan sehingga Poskestren menjadi ujung tombak kesehatan Pesantren.Kata kunci: Analisis, Poskestren, Medan